Collagen/Beta-Tricalcium Phosphate Based Synthetic Bone Grafts via Dehydrothermal Processing - Sarikaya, Burcu; Aydin, Halil Murat (Wiley, 2015)
Millions of patients worldwide remain inadequately treated for bone defects related to factors such as disease or trauma. The drawbacks of metallic implant and autograft/allograft use have steered therapeutic approaches towards tissue engineering solutions involving tissue regeneration scaffolds. This study proposes a composite scaffold with properties tailored to address the macro- and microenvironmental conditions deemed necessary for successful regeneration of bone in defect areas. The biodegradable scaffold composed of porous beta-tricalcium phosphate particles and collagen type I fibers is prepared from a mixture of collagen type-I andβ-tricalcium phosphate (β-TCP) particles via lyophilization, followed by dehydrothermal (DHT) processing. The effects of both sterilization via gamma radiation and the use of DHT processing to achieve cross-linking were investigated. The impact of the chosen fabrication methods on scaffold microstructure andβ-TCP particle-collagen fiber combinations were analyzed using X-ray diffractometry (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and microcomputerized tomography (µ-CT). Electron spinning resonance (ESR) analysis was used to investigate free radicals formation following sterilization. Results revealed that the highly porous (65% porosity at an average of 100 µm pore size), mechanically adequate, and biocompatible scaffolds can be utilized for bone defect repairs.
Keywords: Calcium Phosphates; Bone Transplantation; Tissue Engineering; Tissue Scaffolds; X-Ray Microtomography; Collagen Type I; Biomechanical Phenomena; Cell Line; Cross-Linking Reagents; Freeze Drying; Bone Substitutes; Materials Testing; Spectroscopy, Fourier Transform Infrared; Humans; Porosity; Research Article